2021
DOI: 10.37856/bja.v96i3.4285
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physical Properties in a Long-Term Conservation System for Onion

Abstract: The objective of this study was to evaluate soil physical properties under different cropping systems for onion. The study was conducted on an Inceptisol in Ituporanga, Santa Catarina state, Brazil. We evaluated eight cropping systems for onion: T1: maize-onion succession; T2: common vetch-maize/rye+fodder radish-onion-maize/rye+fodder radish-common bean; T3: rye-onionmaize/black oat-maize; T4: onion-velvet bean succession; T5: rye-onion-millet/black oat-onionmillet; T6: rye-onion-velvet bean succession; T7: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…For POC, at the 0-5 cm layer, all the treatments were similar, however, despite the absence of significant differences in this layer, it´s important to highlight that T4 (onion-velvet bean succession) presented the highest POC concentration, with a value corresponding to 2.8 times the T8 (maize-onion succession in CTS) value which presented the minimum concentration. The minimum POC concentration presented by T8 may be justified by the use of chisel and rotary tiller which deteriorates the soil structure mainly at the soil surface layer as also verified in this experiment by Muetanene et al (2021).…”
Section: Resultssupporting
confidence: 74%
“…For POC, at the 0-5 cm layer, all the treatments were similar, however, despite the absence of significant differences in this layer, it´s important to highlight that T4 (onion-velvet bean succession) presented the highest POC concentration, with a value corresponding to 2.8 times the T8 (maize-onion succession in CTS) value which presented the minimum concentration. The minimum POC concentration presented by T8 may be justified by the use of chisel and rotary tiller which deteriorates the soil structure mainly at the soil surface layer as also verified in this experiment by Muetanene et al (2021).…”
Section: Resultssupporting
confidence: 74%
“…For onion, cover crop residues are deposited between plant rows, especially in late Winter and early Spring, residues protect the soil surface from the impact of raindrops and reduces erosion, suppresses the incidence of weeds, and increases water storage in the soil profile (Chen et al, 2014). Several long-term studies in different Brazilian regions, climates and soils have shown that the continuous use of NTS may improve the chemical (Rheinheimer et al, 2019), physical (Reichert et al, 2016;Pires et al, 2017;Muetanene et al, 2021;) and biological soil properties (Balota et al, 2014;Demetrio et al, 2020), and increase the soil organic matter stock (Ferreira et al, 2018;Veloso et al, 2020), with its corresponding social and environmental advantages (Freitas and Landers, 2014). Thus, NTS has proven to be a reference in soil and water conservation management in Brazilian agriculture (Freitas and Landers, 2014) as well as globally (Derpsch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%